THE ROLE OF ENVIRONMENTAL MANAGEMENT ACCOUNTING IN SUPPORTING COMPANY ENVIRONMENTAL PERFORMANCE - Yanuar Ramadhan; Novita Rini Kumalasari; Kurnia Hidayanti (RADJA PUBLIKA, 2025)
This study aims to analyze the strategic role of Environmental Management Accounting (EMA) in supporting corporate Environmental Performance (EP). With the increasing importance of environmental sustainability and pressure from stakeholders, companies are encouraged to integrate environmental accountability into their decision-making processes, particularly in addressing global issues such as the increase in electronic waste (e-waste). Using a Systematic Literature Review (SLR) of 20 research articles published between 2021 and 2025, the results of this study indicate that EMA has a significant positive impact on corporate environmental performance. EMA serves as a comprehensive information system that identifies, measures, and analyzes environmental costs (monetary) and physical data (such as waste and emissions). The implementation of EMA not only helps companies manage resources efficiently, reduce waste, and improve regulatory compliance, but also encourages Green Innovation, which acts as a key mediating pathway for improving environmental performance. The effectiveness of EMA is strengthened by several factors, namely top management support, institutional and regulatory pressure, and stakeholder integration. In addition, the influence of EMA on environmental performance is found to be stronger in developing countries compared to developed countries. Conceptually, the role of EMA is supported by Legitimacy Theory and Stakeholder Theory, as well as the Natural Resource-Based View (NRBV) perspective. Thus, this study confirms that EMA is an essential strategic sustainability tool in supporting the achievement of Sustainable Development Goals (SDGs) 12 and 13, namely Responsible Consumption and Production and Addressing Climate Change.